Minor rheumatology: Nonsystemic rheumatic disease of juxta-articular soft tissues of the upper extremity. Part 1 - A. E. Karateev; D. E. Karateev; E. S. Orlova; Yu. A. Ermakova (Современная ревматология, 2015)
Rheumatic diseases of juxta-articular soft tissues (RDJAST) (tendinitis, tenosynovitis, bursitis, etc.) are one of the most common causes of disability and one the most common reasons for seeking medical advice. To manage patients with RDJAST is an important part of practising rheumatologists’ work. But unfortunately, the issues of diagnosis and therapy of this pathology have been relatively rarely discussed on the pages of Russian medical journals and at the scientific congresses and conferences of rheumatologists in recent years. This review is to refresh physicians’interest in this problem. Part 1 of this review briefly considers the general issues relating to the epidemiology, pathogenesis, and diagnosis of RDJAST of the upper extremity, such as rotator cuff tendinitis, lateral and medial epicondylitis, stenosing flexor tenosynovitis, de Quervain’s syndrome, and carpal tunnel syndrome.